2017
DOI: 10.1111/jocn.13807
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of communication with older people in home care: A qualitative analysis of audio recordings of home care visits

Abstract: Being responsive to older people's subjective experiences is important in meeting their needs in home care. Communication that addresses the need for trust and predictability is important for older people. Responding to existential needs require more attention. The home care setting has an impact on communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…This paper is based on an international research project, the COMHOME study, which focus on how older persons communicate with their care providers [ 25 ]. Qualitative studies from COMHOME show that communication in home care mainly is instrumental, focusing on the task at hand [ 26 , 27 ], similar to reported findings 20 years ago [ 28 ]. A study, from Sweden and Denmark found that in home help visits, task completion aims at being “good enough” rather than “brilliant” and that older persons rarely dispute the home help provider’s assessment of the task performed [ 29 ].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…This paper is based on an international research project, the COMHOME study, which focus on how older persons communicate with their care providers [ 25 ]. Qualitative studies from COMHOME show that communication in home care mainly is instrumental, focusing on the task at hand [ 26 , 27 ], similar to reported findings 20 years ago [ 28 ]. A study, from Sweden and Denmark found that in home help visits, task completion aims at being “good enough” rather than “brilliant” and that older persons rarely dispute the home help provider’s assessment of the task performed [ 29 ].…”
Section: Introductionsupporting
confidence: 70%
“…What type of responses older persons prefer and perceive as supportive in different situations are yet to be explored. However, increased communication skills may have the potential to enhance the experienced quality of care [ 7 , 8 ], prevent unnecessary suffering [ 65 ] and increase the nursing staff’s perception of being competent when facing challenging communication in home care [ 26 , 27 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found it important to refrain from trying to "solve" a problem and instead maintain a presence and confirming attitude. The importance of existential dialogue was also demonstrated by Kristensen et al [41] who stated that dialogue often breaks down between caregivers and older patients. When older adults want to talk about the end of life, they take initiative to talk about it.…”
Section: Involvement In Social Relationshipsmentioning
confidence: 89%
“…During home care visits, older people reveal essential information about their well‐being and health, such as worries and needs (Kristensen et al, ; Sundler, Höglander, Eklund, Eide, & Holmström, ). These issues can then be listened to and solved by the nursing staff (Höglander, Eklund, Eide, Holmström, & Sundler, ).…”
Section: Introductionmentioning
confidence: 99%